Crossing an Apparent Chasm: Bridging Mindful and Less-Mindful Perspectives on Organizational Learning - Levinthal, Daniel; Rerup, Claus (Organization Science, 2006)
An important new stream of organizational research has emerged in recent years that draws on the notion of mindfulness. At the same time, there is a long-standing body of work in the organizations literature that emphasizes the role of routine-driven, or less-mindful, behavior. We attempt to connect these two seemingly disparate literatures arguing that, at a performative level, important elements of less-mindful processes are necessary elements underlying mindfulness. In particular, we note the role of established action repertories that facilitate the response to novel stimuli and how routines and established role structures enable mindfulness to be sustained across time and the span of the organization. Similarly, we note important elements of mindfulness that underlie less-mindful behavior, highlighting in particular the role of mindfulness in interpreting one’s context so as to identify what constitutes appropriate action in a given circumstance and in interpreting outcomes that form the basis for processes of reinforcement learning. Although we emphasize the complementarity between the two perspectives, we also note points of tension regarding the opportunity costs of mindfulness and the theories’ implied normative claims.